Evaluation of viability and nutritive value of Indigofera tinctoria as a potential animal feeding in Aceh Province, Indonesia - M. Aman Yaman; M. Daud; . Zulfan; Yadi Jufri; T. Fadrial Karmil (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
A series of studies related to animal feeding technology to stimulate the egg production and egg quality with the development of a cheap source of protein types and useful has been done through the evaluation of viabilityand nutritive value of Indigofera tinctoria and in vivo treatments on quail and chicken. Research conducted since 2010 to October 2012 with a focus on increasing the ability to grow the Indigofera’s seed under soaking treatment inauxin hormone and testing the nutritional value on quail and chicken. The first study related to the viability testing is done by soaking the seed of Indigofera in auxin hormone before planting in the field. The study consisted of 4treatments and 5 replications of soaking period, namely: control, B (12 hours), C (24 hours) and D (32 hours) in the solution. The parameters measured were: viability and growth of seed and dry matter content of Indigofera leaf. Thesecond study tested the nutritive value of Indigofera in the ration of laying chickens and quail. Treatments were: 0, 2, 4 and 6% of Indigofera leaf in the ration. Parameters observed in were: egg production, fertility, hatchability andegg quality. The results showed that the viability of the Indigofera’s seed with soaking treatment significantly increased to 80% and soaking for 32 hours resulted a higher viability. The treatment of soaking in auxin hormonealso increased nutrient content of indigofera leaf especially protein. In terms of nutritional value, supplement of Indigofera leaf was very useful to improve the production and quality of eggs in both local laying chickens and quail.The addition of Indigofera leaf in the ration up to 5% also reduced the feed consumption and increasead Haugh unit of egg chicken. From these results it was concluded that the viability of Indigofera tinctoria increased by soaking inauxin hormone for 12-32 hours. These treatments also stimulated the dry matter and protein contents in Indigofera’s leaf. The supplement of Indigofera tinctoria leaf as much as 1-5% in the ration also improved the egg production and quality of local chicken and quail. It was indicated that Indigofera tinctoria contains not only protein and amino acids but also vitamin and mineral for egg quality